Ambient Particulate Matter Air Pollution and Cardiopulmonary Diseases - Thurston, George; Lippmann, Morton (Seminars in Respiratory and Critical Care Medicine, 2015)
Population exposures to ambient outdoor particulate matter (PM) air pollution have been assessed to represent a major burden on global health. Ambient PM is a diverse class of air pollution, with characteristics and health implications that can vary depending on a host of factors, including a particle's original source of emission or formation. The penetration of inhaled particles into the thorax is dependent on their deposition in the upper respiratory tract during inspiration, which varies with particle size, flow rate and tidal volume, and in vivo airway dimensions. All of these factors can be quite variable from person to person, depending on age, transient illness, cigarette smoke and other short-term toxicant exposures that cause transient bronchoconstriction, and occupational history associated with loss of lung function or cumulative injury. The adverse effects of inhaled PM can result from both short-term (acute) and long-term (chronic) exposures to PM, and can range from relatively minor, such as increased symptoms, to very severe effects, including increased risk of premature mortality and decreased life expectancy from long-term exposure. Control of the most toxic PM components can therefore provide major health benefits, and can help guide the selection of the most human health optimal air quality control and climate change mitigation policy measures. As such, a continued improvement in our understanding of the nature and types of PM that are most dangerous to health, and the mechanism(s) of their respective health effects, is an important public health goal.
Keywords: particulate matter; lung deposition; morbidity; mortality; climate co-benefits